2011
DOI: 10.3109/08820139.2011.619021
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis and Killing of Salmonella by 7-Hydroxycoumarin Activated Macrophages

Abstract: Coumarin and its derivatives have potent immunomodulatory activities. Here we describe the parameters of the protective effect of 7-hydroxycoumarin (7-OHC) in experimental Salmonella enterica Serovar Typhimurium infection in mice. The protective effect depended on the duration of treatment reaching its maximum after 10 days of pretreatment and lasted for at least 15 days after its end. Electron microscopy studies revealed that 7-OHC induced ultrastructural changes in macrophages consistent with their activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…UMB also reduces the incidence of lymphoedema in humans [14] . Of note, antioxidative, anti-inflammatory and immunomodulatory effects of UMB in both, in vitro and in vivo studies have been reported elsewhere [8,[15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…UMB also reduces the incidence of lymphoedema in humans [14] . Of note, antioxidative, anti-inflammatory and immunomodulatory effects of UMB in both, in vitro and in vivo studies have been reported elsewhere [8,[15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Previously several studies showed that umbelliferone exerts anti-inflammatory, antioxidant, antidiabetic, antinociceptive, and anticancer effects [ 27 ]. Moreover, the effects of umbelliferone on bacteria have been also reported [ 28 30 ]. Stefanova et al in an experimental study, using Salmonella enterica serovar Typhimurium infection in mice, documented that 7-hydroxycoumarin pretreatment is able to reduce both tissue damaging and immunosuppressive effects of the oxidative stress related to the infection [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effects of umbelliferone on bacteria have been also reported [ 28 30 ]. Stefanova et al in an experimental study, using Salmonella enterica serovar Typhimurium infection in mice, documented that 7-hydroxycoumarin pretreatment is able to reduce both tissue damaging and immunosuppressive effects of the oxidative stress related to the infection [ 28 ]. Lee and coworkers showed that umbelliferone is able to inhibit biofilm E. coli O157:H7 formation by more than 80% [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some members of this family exhibit cell toxicity that has been harnessed in anti-tumor applications 103-105 , while others do not. A modeling approach similar to that presented herein would shed light on the molecular mechanisms underlying differential membrane-mediated toxicity of these compounds.…”
Section: Conclusion and Summarymentioning
confidence: 99%